2020
DOI: 10.1093/cercor/bhaa007
|View full text |Cite
|
Sign up to set email alerts
|

Frequency- and State-Dependent Network Effects of Electrical Stimulation Targeting the Ventral Tegmental Area in Macaques

Abstract: The ventral tegmental area (VTA) is a midbrain structure at the heart of the dopaminergic system underlying adaptive behavior. Endogenous firing rates of dopamine cells in the VTA vary from fast phasic bursts to slow tonic activity. Artificial perturbations of the VTA, through electrical or optogenetic stimulation methods, generate different and sometimes even contrasting behavioral outcomes depending on stimulation parameters such as frequency, amplitude, and pulse width. Here, we investigate the global funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 58 publications
(105 reference statements)
4
40
1
Order By: Relevance
“…However, it is also possible that our imaging methods limited the ability to detect contralateral activations. Indeed, other studies have shown some contralateral activations induced by EM, consistent with anatomical connections across hemispheres (Ekstrom et al, 2008;Moeller et al, 2008;Premereur et al, 2015;Murris et al, 2020). As expected for the EM of striatal regions, the activated areas were known constituents of the basal ganglia circuit (Draganski et al, 2008;Haber & Knutson, 2010).…”
Section: Performance Of the Microdrive During Em-coupled Mri Scanningsupporting
confidence: 78%
“…However, it is also possible that our imaging methods limited the ability to detect contralateral activations. Indeed, other studies have shown some contralateral activations induced by EM, consistent with anatomical connections across hemispheres (Ekstrom et al, 2008;Moeller et al, 2008;Premereur et al, 2015;Murris et al, 2020). As expected for the EM of striatal regions, the activated areas were known constituents of the basal ganglia circuit (Draganski et al, 2008;Haber & Knutson, 2010).…”
Section: Performance Of the Microdrive During Em-coupled Mri Scanningsupporting
confidence: 78%
“…Particularly, the strength of stimulation effects is modulated by the brain state (e.g. anaesthetized vs. awake) (Murris et al, 2020), the properties of the employed visual stimuli such as contrast or the visual responsiveness of activated voxels (Ekstrom et al, 2009(Ekstrom et al, , 2008 and task demands (Premereur et al, 2013). The first goal of this study was to identify the shared functional circuitry of dPul and LIP during oculomotor tasks.…”
Section: Highlightsmentioning
confidence: 99%
“…An inverted-U relationship between dopamine and distributed working memory activity Previous experimental and modelling studies have shown an inverted-U relationship between D1 receptor stimulation and persistent activity in the prefrontal cortex in monkeys performing working memory tasks (Brunel and Wang 2001;Vijayraghavan et al 2007;Wang et al 2019). Stimulation of VTA (presumably leading to cortical dopamine release) in resting monkeys also has an inverted-U effect on cortical activity in distributed areas across cortex (Murris et al 2020).…”
Section: A Gradient Of D1 Receptors Along the Cortical Hierarchymentioning
confidence: 98%